Observation Of Writing to Learn Strategy On 8th Grade Student's Science Learning - Mardhotillah, Zakky; Muttaqiin, Arief (Universe, 2024)
The aim of this paper is to perceive the implentation of writing to learn strategy on science learning. This study uses quantitative descriptive research. Observations were carried out to see directly how the activities of the teacher convey the subject matter. In the preliminary stage, the percentage of implementation was 83%, the core activity stage was 95%, and the closing was 92%. The core activities in this study were carried out in sequential activity steps namely; observing, questioning, gathering information, associating, and communicating results. At the observing stage, the percentage of implementation was 88%, asking questions was 100%. Collecting information is 96%, associating is 100%, and communicating is 92%. Learning with the strategy of writing to learn has been implemented very well. In general, the teacher has succeeded very well in carrying out science learning activities using the writing to learn strategy.